Clinical and paraclinical manifestation of irratable bowel syndrome in children - Shlyk, O. G.; Tkachuk, S. V.; Hilchevska, V. S.; Korotun, O. P. (Journal of Education, Health and Sport, 2019)
Bowel diseases and disorders take a significant place among digestive system pathology in children. Overall goal of the research is a study of clinical and paraclinical indices for verification of Irritable Bowel Syndrome (IBS) in children.A complex clinical, anamnestic and paraclinical research of 35 children 3 to 16 years aged with IBS was analyzed. IBS with constipation were found in 32 children (91,4%); IBS with pain and flatulence – in 2 children (5,7%); only 1 patient had IBS with diarrhea (2,9%).IBS was found more often in children of preschool and primary school age, was characterized by prolonged relapsing course and same frequency in both genders. Clinical severity of the disease correlated with older age, overweight, signs of dysautonomia (Vegetative-vascular dystonia (VVD)) and cholestasis.